2019
DOI: 10.1080/19420862.2019.1601985
|View full text |Cite
|
Sign up to set email alerts
|

Important roles of CD32 in promoting suppression of IL-4 induced immune responses by a novel anti-IL-4Rα therapeutic antibody

Abstract: Asthma is characterized by airway hyperresponsiveness and inflammation, as well as underlying structural changes to the airways. Interleukin-4 (IL-4) is a key T-helper type 2 (Th2) cytokine that plays important roles in the pathogenesis of atopic and eosinophilic asthma. We developed a novel humanized anti-IL-4Rα antibody that can potently inhibit IL-4/IL-13-mediated TF-1 cell proliferation. Using monocytes isolated from human peripheral blood mononuclear cells (PBMCs), we revealed a critical role of CD32 in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…The half-maximal inhibitory concentration for NM26-2198 was comparable with that of dupilumab, which is also an IgG4. An Fc-silenced version of NM26-2198 (PRO2142) demonstrated a significant decrease in activity in this assay, particularly in monocytes, consistent with previous studies showing that Fc binding to FcγRII is essential for inhibition of IL-4–induced upregulation of CD23 in immune cells ( Zhao et al, 2019 ). These experiments demonstrate that NM26-2198 retained FcγRII binding.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The half-maximal inhibitory concentration for NM26-2198 was comparable with that of dupilumab, which is also an IgG4. An Fc-silenced version of NM26-2198 (PRO2142) demonstrated a significant decrease in activity in this assay, particularly in monocytes, consistent with previous studies showing that Fc binding to FcγRII is essential for inhibition of IL-4–induced upregulation of CD23 in immune cells ( Zhao et al, 2019 ). These experiments demonstrate that NM26-2198 retained FcγRII binding.…”
Section: Resultssupporting
confidence: 89%
“…One of the hallmarks of IL-4– and IL-13–induced immune responses is upregulation of CD23 (the low-affinity IgE receptor, FcεRII) on monocytes and B cells ( Defrance et al, 1994 ; McCormick and Heller, 2015 ; Moyle et al, 2019 ). Anti–IL-4Rα antibodies have been shown to inhibit IL-4–induced CD23 upregulation, but their potency depends on the characteristics of antibody binding to FcγRII (CD32) ( Zhao et al, 2019 ). Because NM26-2198 has an IgG4 isotype Fc moiety and has anti–IL-31 single-chain variable fragments attached to its C termini, it was important to assess its potency for inhibition of CD23 upregulation.…”
Section: Resultsmentioning
confidence: 99%
“…The Th2-type T cells mediate airway allergic inflammation by producing IL-4, IL-5, IL-10, and IL-13. It has been reported that IL-4 can regulate the expression of CD23 in normal B cells (36) and induce IgE production (37); therefore, we investigated the regulation of CD23 in HEI-OC1 cell lines by IL-4. First, the viability of HEI-OC1 cells was greater than 80% at 12, 24, and 36 h after IL-4 (10, 15, 20, 50, 100 ng/ml) stimulation, and it was not different in each group (Fig.…”
Section: Il-4 Enhances Ige Transcytosismentioning
confidence: 99%
“…Endolymphatic hydrops underlies the classic pathological characteristic of the disease. Several factors have been postulated to be involved in the development of MD, including viral infections, allergies, family history, and autoimmunity (36). However, most of the studies are limited by a lack of population-based cohorts and a low number of cases and inner ear tissue specimens.…”
mentioning
confidence: 99%
“…Significantly, IL-4 was elevated in convalescent patients within the first week after discharge ( p = 0.036) and continued to stay high at week 2 ( p = 0.022) ( Figure 3 ), even though IL-4 had no significant fluctuation through the viral replication phase as previously reported ( 1 ). IL-4 plays a key role in promoting naïve T cells to develop into Th2-like cells ( 18 ) and immunoglobulin class-switching from IgM to IgE and IgG ( 19 ). The observed elevation of IL-4 might suggest that there is a differential set of regulatory T cell and B cell immune responses occurring in early convalescence of COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%